Improving Express Packaging Recycling in Live-Streaming E-Commerce: A Triple Evolutionary Game and Simulation Analysis - Zhang, Weisi; Kong, Jiahao; Du, Bin; Li, Leyao (International Journal of Industrial Engineering: Theory, Applications and Practice, 2026)
The low recycling rates of express packaging are worsened by the rise of live-streaming e-commerce. This study investigates the effects of stream pushing by platforms, recycling rewards, and merchants’ freight insurance on consumer recycling behavior. A tripartite evolutionary game model involving platforms, merchants, and consumers was developed, incorporating stochastic differential equations. Results show that active stream pushing by platforms significantly boosts consumer recycling participation. Merchants who offer return freight insurance encourage higher recycling rates, creating a win-win situation with consumers. Additionally, moderate recycling rewards can enhance recycling rates, but excessively high rewards may reduce platforms’ incentive for stream pushing, ultimately hindering recycling efforts.